Is IL-6 the best pro-inflammatory biomarker of clinical outcomes of cancer cachexia? - Scheede-Bergdahl, Celena; Watt, Heather L.; Trutschnigg, Barbara; Kilgour, Robert D.; Haggarty, Allison; Lucar, Enriqueta; Vigano, Antonio (Clinical nutrition (Edinburgh, Scotland), 2012)
Despite the descriptive presence of cancer cachexia (CC) in clinical practice, the underlying mechanisms and diagnostic definition have not been clearly identified. Recent work, attempting to establish diagnostic and staging criteria for CC, has identified IL-6 as a biomarker. This study aimed to investigate the clinical relevance of plasma levels of four pro-inflammatory cytokines (IL-6, IL-1β, IL-8 and TNF-α) in advanced cancer patients (ACP) to further establish their potential in the diagnostic definition of CC. Blood was obtained from 83 ACP (47 male and 36 female, aged 34–85 years) and analyzed for white blood cells, lymphocytes, C-reactive protein, albumin and cytokines. Subjects completed questionnaires to establish weakness, loss of appetite, fatigue, quality of life and weight loss; completed tests to determine strength, body composition and sarcopenia; and consented to chart review to calculate survival and total days admitted to hospital. This study shows that, in ACP, IL-1β is better associated with clinical features of the cachectic condition, such as weakness, loss of appetite, weight loss and sarcopenia, than IL-6. IL-6 may not best represent the clinical correlates of CC in ACP. Additional cytokines should be considered in the definition of this condition.